Career Preference and Factors Influencing Career Choice among Undergraduate Pharmacy Students at University of Khartoum, Sudan - Ahmed H. Arbab; Yasir A. M. Eltahir; Fatima S. Elsadig; Bashir A. Yousef (MDPI AG, 2022)
The pharmacy profession has expanded and adapted to changes in community needs. Although career planning and understanding the determinants of career choice are essential, there remains a lack of studies exploring factors influencing future career plans. This study was conducted to identify career preferences and factors influencing future career choices among undergraduate pharmacy students. A cross-sectional study was carried out at the Faculty of Pharmacy, University of Khartoum. A self-administered questionnaire was used to collect data from randomly selected participants. Out of 220 respondents, 85.9% were females. The average age of the respondents was 21.7 ± 1.5 years. Clinical pharmacy was selected as the most preferred future career domain (30%), followed by academia and research (12%), the pharmaceutical industry (11%), and community pharmacy (10.5). Approximately 20% of participants reported a preference for moving abroad for work. Regarding factors influencing future career domain choice, participants ranked training in the workplace (80%) and curriculum content (70%) as the top faculty-related factors, while interaction with practicing pharmacists (71.8%) and salary (78%) were the major personal-related and job-related factors. This study emphasized the importance of understanding job preferences and the factors influencing career choice, and could be useful in ensuring a future balance between professional domains and meeting society's evolving expectations.